2006
DOI: 10.3748/wjg.v12.i31.4981
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of caffeic acid phenethyl ester on the growth of SW480 colorectal tumor cells involves β-catenin associated signaling pathway down-regulation

Abstract: CAPE can inhibit SW480 cell proliferation by inducing cell cycle arrest and apoptosis. Decreased beta-catenin and the associated signaling pathway target gene expression may mediate the anti-tumor effects of CAPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
5
28
0
2
Order By: Relevance
“…Wang et al [68] suggested that the obtained results are due to the induction of suppression of b-catenin level in cytosol and nucleus. Similar results were achieved in a study by He et al [69]. CAPE (2.5-80 mg/L) inhibited the proliferation of SW480 colorectal cancer cells by the reduction of b-catenin expression and suppression of cyclin D1 and c-myc protein expression.…”
Section: Effect Of Propolis Compounds On Cancer Cells Proliferationsupporting
confidence: 89%
“…Wang et al [68] suggested that the obtained results are due to the induction of suppression of b-catenin level in cytosol and nucleus. Similar results were achieved in a study by He et al [69]. CAPE (2.5-80 mg/L) inhibited the proliferation of SW480 colorectal cancer cells by the reduction of b-catenin expression and suppression of cyclin D1 and c-myc protein expression.…”
Section: Effect Of Propolis Compounds On Cancer Cells Proliferationsupporting
confidence: 89%
“…Colorectal cancer is the third leading cancer and the fourth most frequent cancer-related death worldwide [1,2]. Moreover, the incidence of colorectal cancer has rapidly increased in Asian population like Chinese people [3].…”
Section: Introductionmentioning
confidence: 99%
“…The same group has also showed the loss of mitochondrial membrane potential to about half of the untreated level in response to CAPE only after 6 h in HL60 cells (Chen et al 2001). It was reported by several groups that CAPE inhibited cell growth and proliferation and triggered apoptosis in SW480 and HCT116 colorectal cancer cells, ME180 cervical cancer cells, C6 glioma cells, and MCF-7 breast cancer cell (He et al 2006;Wang et al 2005;Hung et al 2003;Lee et al 2003;Watabe et al 2004;Burke et al 1995). On other hand, it was shown by Chung and his coworkers that besides inhibition of cell proliferation, CAPE also has inhibitory effects on invasion and metastasis through suppression of MMP-9 enzyme and downregulation of expression of NF-KB (Chung et al 2004).…”
Section: Discussionmentioning
confidence: 82%